IIMPLEMENTATION OF LEGAL CERTAINTY ON COMPARATIVE STUDIES OF IJARAH MUNTAHIYA BITTAMLIK & RENTAL CONTRACT - Moh. Nurul Huda; Muhammad Ridwan Lubis (Jurnal Akta, 2021)
In recent times, it has become common among the public regarding the Ijarah Muntahiya Bittamlik (IMBT) contract. IMBT is a contract similar to a lease and purchase agreement. In practice in the community, these two contracts are carried out by means of renting first and ending with buying and selling. Although, in general they have similarities, these two agreements have differences that have different consequences. The research method used in this study is doctrinal legal research with a comparative law approach. The results of this study indicate that the IMBT contract has more legal certainty than the lease-purchase agreement. This is because the IMBT contract has provisions regulated in the Sharia Banking Law, the Sharia Economic Law Compilation, and PSAK No. 107 concerning Ijarah and IMBT accounting, while the lease purchase agreement is only based on the principle of freedom of contract. The implementation of the IMBT contract also has more legal certainty, considering that dispute resolution efforts can be carried out through the provisions of Article 283 and Article 284 of the KHES by carrying out sales of the disputed object. This is different from a lease-purchase agreement, where dispute resolution efforts are generally carried out through unilateral withdrawals and the agreement also contains standard clauses that have the potential to violate Article 18 of the Consumer Protection Law.